Assessing Landscape Sensitivity Based on Fragmentation Caused by the Artificial Barriers in Hungary - Bata, Teodóra; Mezősi, Gábor (Journal of Environmental Geography, 2013)
Artificial barriers significantly disturb the landscape unit. Roads split the contiguous landscape units, thus basically modi fying their ecological characters. The more artificial barriers are constructed in the landscape, the more fragmented it is. Theref ore, the contiguous landscape unit is divided into two or more patches, weakening resilience and stability of ecological systems. During decrease in patch size, the stability reduces until the patch size is at its minimum viable or effective population size. In current study analysing the degree of fragmentation caused by artificial barriers in meso-scale landscape units (meso-regions) we can get an overall picture about changes in their stability and sensitivity. The major aims of this study is to investigate the fragmentation of landscape units caused by three types of artificial barriers (roads, railways and settlements) in micro-regions, and to measure the degree of fragmentation and its spatial-temporal (1990, 2011 and future scenario to 2027) changes using mathemat ical/ statistical analysis and landscape metrics (Number of Patches, Division, Landscape Splitting Index and Effective Mesh Size). By calculating landscape fragmentation metrics, the micro-regions are identified, which must be protected with high priority in the future. In the planning processes, type and position of artificial barriers could be more properly determined by calculation of these landscape metrics.